Structure and properties of TiSiCN coatings with different bias voltages by arc ion plating. (5th March 2018) - Xie, Xinming; Li, Jinlong; Dong, Minpeng; Zhang, Henghua; Wang, Liping
Abstract: TiSiCN coatings were deposited on 316 L steel using the multi-arc ion plating system. All the coatings had the same total thickness of approximately 1.6 µ m. The TiSiCN coatings were deposited under the mixture constant flow of N2 and C2 H2 but varying bias. Information about structures, composition and properties were characterized by scanning electron microscope, x-ray diffraction, x-ray photoelectron spectroscopy, nanoindentation and ball-on-plate wear tests. The results show that all of the coatings consist of a TiCN nano-crystal phase and an Si3 N4 amorphous phase. With an increase in the bias, the film becomes denser and exhibits better tribological behavior and mechanical properties. Moreover, the bonding strength between the coatings and the substrate increased and the resistance to thermal shock intensified when the coatings were made at a higher bias voltage.